GRAPHIC DESIGN IN VIETNAM IN INTEGRATION AND SUSTAINABLE DEVELOPMENT - Ngoc, Nguyen Hong; Huong, Nguyen Thi Lan (Revista Prâksis, 2024)
The research focuses on studying the progress of graphic design in Vietnam in the context of integration and sustainable development. By combining survey and expert interview methods, along with comparisons with international standards, the study evaluates the development, challenges, and causes of issues in the field of modern graphic design in Vietnam. The research results show significant progress in this field, but also reveal several weaknesses such as imitation, replication, and a lack of understanding of the nation's cultural and aesthetic language. Through analysis and discussion, the study proposes some potential directions for the development of graphic design in Vietnam, aiming to enhance creativity, sustainability, and accurately reflect the cultural identity of the country. The conclusion emphasizes the necessity of promoting innovation and international cooperation in the field of graphic design to foster sustainable development in the future.